Identification of Some Distinctive Values of Acehnese Malee (Shyness) for Character Education - Abubakar, Abubakar; Srimulyani, Eka; Anwar, Anwar (SCAD Independent, 2019)
The aim of this research is to identify some values of malee as a part of character education. This research used qualitative approach. The sampel of this research are principals, senior teachers, the Chairman of Aceh Adat Council (MAA) and students in MTsN Kota Banda Aceh. Data were collected by in-depth interview technique, documentation, and corroborated by focus group discussion. The data analysis was held on three stages: data reduction, data display, and data verification and conclusion. The research results showed that there are several malee values that can be used to shape students character in the school, namely: Malee hana shalat (shyness for not doing a prayer), Malee hana puasa (shyness for not doing fasting) Malee Meurukok and mabok (shyness for smoking and getting drunk, Malee kriet (shyness for being stingy), Malee meusulet (shyness for telling a lie) Malee peukaru ngon (shyness for disrupting friend), Malee dendam (shyness for taking a revenge), Malee kuto (shyness for dirty), Malee keuguree (shyness to the reacher/respecting teacher). Malee meucewek (shyness for dating). Malee value has a strong foundation in character building, because it pertains to their daily faith and worship. And, it has social and religious sanctions for those who violate it.